Measuring Performance Efficiency of Oil Palm Plantations using Window Analysis - Razman, Mat Tahar; Cheng, Jack Kie; Ahmad Borhan, Ahmad Nordin (Malaysian Palm Oil Board, 2013)
Performance of a unit or an organisation is among the issues discussed as a way of helping the decision-making process. This study was aimed at determining and evaluating performance efficiency trends in the management of selected plantations in the oil palm industry. It took into account the input and output factors using data envelopment analysis (DEA). Relative efficiency was identified to set the benchmark in this case study, and as a way to improve the overall activities related to the use of input as resources by the least efficient plantation. The DEA method was used to calculate the efficiency trend score. Data collected were from the years 2001-2010 for five input and one output variables. Analysis was conducted using the Window Analysis, DEA Solver. The overall result shows significant correlations among the variables and that the average efficiency score determines efficiency trend. Two out of three plantations studied had highest average efficiency scores while the other one was the less efficient.